2020
DOI: 10.1152/ajpcell.00494.2019
|View full text |Cite
|
Sign up to set email alerts
|

Electrically stimulated contractile activity-induced transcriptomic responses and metabolic remodeling in C2C12 myotubes: twitch vs. tetanic contractions

Abstract: The contraction of myotubes using electrical pulse stimulation is a research tool used to mimic muscle contractile activity and exercise in rodents and humans. Most protocols employed in previous work used low-frequency twitch contractions. However, high-frequency tetanus contractions that are more physiologically relevant to muscle contractions in vivo are poorly characterized. In this report, the similarities and differences in acute responses and chronic adaptations with different contractile modes using tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 46 publications
2
33
0
Order By: Relevance
“…Increased mitochrondrial content/function is an important adaptation of habitual endurance exercise. Our results showed that mitochondrial biogenesis as measured by MitoTracker staining, COX activity and Cyt C (a critical protein in oxidatve phosphorylation) was increased in chronically stimulated myotubes, in line with reporter results by other groups [31], [32], [45], [46]. In general, our results validated that the chronic stimulation protocol was effective in mimicing the effects of chronic contractile activity in vitro , and we subsequently used it to interrogate the effects of contractile activity on Skm-EVs.…”
Section: Discussionsupporting
confidence: 92%
“…Increased mitochrondrial content/function is an important adaptation of habitual endurance exercise. Our results showed that mitochondrial biogenesis as measured by MitoTracker staining, COX activity and Cyt C (a critical protein in oxidatve phosphorylation) was increased in chronically stimulated myotubes, in line with reporter results by other groups [31], [32], [45], [46]. In general, our results validated that the chronic stimulation protocol was effective in mimicing the effects of chronic contractile activity in vitro , and we subsequently used it to interrogate the effects of contractile activity on Skm-EVs.…”
Section: Discussionsupporting
confidence: 92%
“…Lactate [ 7 , 8 , 9 ], fibronectin type III domain-containing protein 5 (FNDC5)/irisin [ 10 ], and cathepsin B (CTSB) [ 11 ] are myokines associated with brain function. Specifically, lactate is secreted from skeletal muscle by mechanical muscle contractile stimulation in both in vitro [ 12 , 13 ] and in vivo [ 8 , 14 ] studies. Secreted lactate is delivered into the brain through blood vessels by crossing the blood-brain barrier (BBB) [ 15 , 16 ], which increases BDNF expression in the brain [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…EPS induces calcium release from the sarcoplasmic reticulum, therefore EPS enables analysis of calcium signaling in vitro. Global transcriptional analyses of EPS have recently been published by two different groups [21,22]. Both experiments focused on relatively short-term EPS treatments.…”
Section: Introductionmentioning
confidence: 99%